UNCHARTED WATERS: ANALYZING PRESIDENT BUHARI'S DIPLOMATIC ADAPTATIONS TO INTERNATIONAL SECURITY THREATS, 2015-2023 - ENUEME PAUL OVIE; GBIGBIDJE DAVID LAWSON (International Studies Journal)
This study examines how Nigeria’s foreign policy under President MuhammaduBuhari adapted to the global challenges that emerged from 2015 to 2023, filling a gap in the literature on adaptive foreign policy theory in the African context. The study is rooted in the theoretical framework of adaptive foreign policy theory, which asserts the need for nations to flexibly adjust their foreign policy objectives and approaches in response to evolving international conditions. The study utilizes a literature-based approach, integrating academic and non-academic sources, to provide a comprehensive analysis of President Buhari's diplomatic adaptations during this critical period. Three overarching themes emerge from the thematic analysis: strategic responses to the US-China Trade War and resultant global economic disruptions, concerted efforts in stabilizing regions affected by coups and political instability in Africa, and a balanced approach towards the Covid-19 pandemic encompassing global health security and national well-being.The findings reveal Nigeria's adeptness in managing the economic impact of the US-China Trade War by diversifying economic partnerships, thereby bolstering economic stability. Additionally, the study underscores Nigeria's diplomatic dexterity in tackling regional instability through a complex foreign policy, which includes diplomatic negotiation with coup leaders, judicious use of sanctions, and strategic deployment of troops. Moreover, Nigeria's response to the Covid-19 pandemic reflects a multifaceted approach that prioritizes both global health security and national welfare. While the study sheds crucial light on Nigeria's global strategy and its adaptability in safeguarding its interests, certain limitations must be acknowledged. The examination is delimited to a specific period and context of Nigeria's foreign policy, potentially limiting its generalizability. Furthermore, reliance on secondary data sources may introduce bias or inaccuracies. To enhance the robustness of these findings, future research should explore different periods, contexts, data sources, and methodological approaches, while considering diverse theoretical frameworks or perspectives.